Volvulus of Small Bowel in a Case of Simple Meconium Ileus - Kayastha, Kanchan (EL-MED-Pub, 2011)
Meconium ileus is one of important causes of neonatal intestinal obstruction. Many patients respond well to nonsurgical management with enemas, however, few patients may develop complications in the postnatal period thus requiring urgent operation. A 2 day old newborn presented with clinical features of intestinal obstruction. There was a suspicion of meconium ileus. Contrast x-ray with gastrografin enema was suggestive of unused colon with beaded appearance. Patient had to be surgery as repeated enemas did not improve the condition and progressive abdominal distension occurred. At exploration twist of the dilated, meconium filled loop of small bowel found. De-twisting of the volvulus done and Bishop Koop ileostomy fashioned. Patient made an uneventful recovery. Stoma was closed six months later.